PENGARUH CORPORATE GOVERNANCE, CAPITAL STURCTURE, DAN GENDER DIVERSITY TERHADAP FIRM PERFORMANCE - Krisyadi, Robby; Anastasya, Anastasya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The success and failure of the company can be influenced based on the firm's performance. Firm Performance can be a measure of the company's level of success in achieving the targeted goals. The purpose of the study was to determine the effect of the board of directors, audit committee, foreign ownership, institutional ownership, board independence, gender diversity, ownership concentration, audit reputation, ceo tenure, and leverage on firm performance in non-financial companies listed on the Indonesia Stock Exchange. The study was conducted on non-financial entities listed on the IDX through www.idx.co.id from 2017 to 2021. The sample results that have been selected contain 1,880 data. The data analysis method in the findings contained in this study uses the SPSS and PLS-SEM applications. The results of the study stated that the board of directors, audit committee, foreign ownership, institutional ownership, board independence, gender diversity, ownership concentration, audit reputation, ceo tenure, and leverage had a significant positive effect on firm performance using tobin's q measurement. However, the ownership concentration variable has no significant effect on firm performance by measuring return on equity.